A cross-sectional observational study assessing the liver function in malarial patients - Mehta, Dhara P.; Shah, Purva C.; Daveshwar, Meena (International Journal of Advances in Medicine, 2021)
Background: Malaria is a major cause of morbidity in the tropics, being a disease of global importance that results in 300-500 million cases annually. Liver involvement manifests as jaundice, hyperbilirubinemia, hepatomegaly and elevated enzymes (transaminases and alkaline phosphatase). Our objective in this study was to evaluate the role of liver function as an indicator of malaria in endemic regions and as a marker of disease severity. Methods: This was an observational cross-sectional study conducted in central laboratory, department of pathology, central laboratory, department of biochemistry, and out-patient department, department of medicine, medical college Baroda and SSG hospital over a period of ten months, from February, 2019 to November, 2019 and included 137 microscopy proven malaria positive cases. The parasite density on peripheral smear was graded as scanty, moderate and heavy. After procuring the records of serum bilirubin, SGPT and SGOT, statistical analysis of the data was performed. Results: All the 3 parameters show maximum derangement in severe parasitemia with mean values of 3.57, 81.44, and 92.9. While comparing vivax and falciparum malaria, all the LFTs studied show greater derangement in Plasmodium Falciparum when compared to Plasmodium vivax, with greatest difference seen in bilirubin levels (27.78% cases with hyperbilirubinemia in Plasmodium vivax versus 71.43% cases of Plasmodium falciparum showing hyperbilirubinemia). Conclusions: We conclude that altered liver function in form of hyperbilirubinemia and increased liver enzymes in a patient with acute febrile illness increase the probability of malaria, hence directing the clinician along the correct path of further work-up and accurate treatment.